Parameters oxidative stress and endogenous intoxication of peripheral blood in patients with exogenous organic disorders in dynamic of the pharmacotherapy - N. M. Krotenko (Bûlleten' Sibirskoj Mediciny, 2012)
Complex clinical-biological investigation has been conducted in 25 patients with exogenous organic disorders and 30 mentally and physically healthy persons. Influence of the metabolic cerebroprotector cortexin on indices of oxidative stress in dynamic of the pharmacotherapy has been investigated. It has been shown that cortexin increases clinical efficacy of complex therapy of patients and exerts positive influence on indices of homeostatic systems. Action of cortexin on indices of the oxidative stress is characterised by normalisation of the processes of peroxide oxidation of lipids in erythrocytes and in serum